Fish - Henrie, Fiona; Findlay, Michael; Henrie, Marc (London ; New York : Franklin Watts, 1980)
Explains how to buy, set up, and maintain a tank for freshwater fish and plants. Health care, feeding, and breeding of fish are briefly discussed.
Includes index.
Keywords: Aquarium fishes -- Juvenile literature; Aquariums -- Juvenile literature; Aquarium fishes; Aquariums